A dialogue between quantum information and thermodynamics - Morris, Benjamin (2021)
Thermodynamics has always been inextricably linked with the abstract concept of information. The past decades have proved this relationship fruitful once again with the incorporation of many concepts and ideas from quantum information theory into the context of thermodynamics. This has allowed us to better understand the role played by uniquely quantum features such as coherence and entanglement in thermodynamics and encouraged us to test some of the fundamental limitations of thermodynamics within quantum physics laboratories. In this thesis I will demonstrate some of these fruits that allow us to both reformulate and test thermodynamics while forcing us to operationally understand the thermodynamic implications of our abstract information based results.